2017
DOI: 10.3389/fpls.2017.00827
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Physiological and Molecular Analyses of Two Contrasting Flue-Cured Tobacco Genotypes under Progressive Drought Stress

Abstract: Drought is a major environmental factor that limits crop growth and productivity. Flue-cured tobacco (Nicotiana tabacum) is one of the most important commercial crops worldwide and its productivity is vulnerable to drought. However, comparative analyses of physiological, biochemical and gene expression changes in flue-cured tobacco varieties differing in drought tolerance under long-term drought stress are scarce. In this study, drought stress responses of two flue-cured tobacco varieties, LJ851 and JX6007, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 54 publications
6
16
0
Order By: Relevance
“…In agreement with our results, [46,47] evidenced that drought stress cause reduction in plant fresh and dry weight in tobacco and tomato plants. Our results are in line with many reports that have stated that drought-tolerant varieties could maintain higher growth than drought-sensitive ones [23].…”
Section: Growth Chlorophyll Content and Lwp Of The Three Tobacco Varsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with our results, [46,47] evidenced that drought stress cause reduction in plant fresh and dry weight in tobacco and tomato plants. Our results are in line with many reports that have stated that drought-tolerant varieties could maintain higher growth than drought-sensitive ones [23].…”
Section: Growth Chlorophyll Content and Lwp Of The Three Tobacco Varsupporting
confidence: 93%
“…Changes of leaf water potential in response to the drought stress were evaluated in various genotypes as shown in Figure 2D, the three varieties showed a clear decrease during 72 h of the drought stress. These findings are supported by [23], as drought stress decreased LWP.…”
Section: Growth Chlorophyll Content and Lwp Of The Three Tobacco Varsupporting
confidence: 62%
See 1 more Smart Citation
“…1D-F). Previous reports have showed that drought stress induced higher H 2 O 2 accumulation, lipid peroxidation and EL in drought-sensitive maize, barley and tobacco genotypes than that in drought-tolerant genotypes [17,30,31]. Similarly, the results from this study indicate that the sorghum genotypes PI 585453, PI 585456 and PI 585452 suffered greater cell membrane damage than other genotypes and demonstrate a possible correlation to drought sensitivity.…”
Section: The Biochemical Aspect Of Drought Response Among Sorghum Gensupporting
confidence: 79%
“…At the moment, soil moisture content was progressively reduced to around 20%. The soil moisture was measured daily using a Soil Moisture Meter (ECA-SW1, TuoPu Bio Co., China) as described previously ( Su et al, 2017 ). And then, these stressed plants were re-watered.…”
Section: Methodsmentioning
confidence: 99%